Konflik Sosial Realistis & Non Realistis Perspektif Lewis A. Coser: Sebuah Kajian pada Web Series Sajadah Panjang Karya Sondang Pratama - Maghfirah, Yulistira Jami’atul; Efendi, Agik Nur (Lingua Skolastika, 2024)
Social conflict is a dispute that occurs between people, within the scope of the family and society. Social conflict does not only have a negative impact on the parties in conflict, there are times when conflict has a positive impact on the parties in conflict. The discussion in this research is, what realistic and non-realistic conflict forms and their resolution. This research examines social conflict through one of the web series literary works entitled Sajadah Panjang by Sondang Pratama which tells the story of various kinds of conflicts that come and go. Based on this, there are two research objectives which are the main study in this research, namely: first, describing realistic forms of conflict and their resolution in the web series Sajadah Panjang by Sondang Pratama from the perspective of Lewis A. Coser. Second, describing non-realistic forms of conflict and their resolution in the Sajadah Panjang web series by Sondang Pratama from the perspective of Lewis A. Coser. The method used in this research is qualitative with a literary sociology approach and uses social conflict theory from Lewis A. Coser's perspective which is more focused on forms of social conflict, namely realistic and non-realistic conflicts. The first result of the discussion in this research is that realistic forms of conflict are divided into two parts, namely hostile behavior and hostile feelings using mediation and tolerance for conflict resolution. Second, non-realistic forms of conflict are resolved using conversion and mediation conflict resolution.